Nobel committee honors tumor immunologists - Anand Rotte; Gabriella D’Orazi; Madhuri Bhandaru (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract This commentary wishes to highlight the 2018 Nobel Prize in Medicine awarded to two cancer immunotherapy scientists, Prof James Allison and Prof Tasuku Honjo, for their discovery on unleashing the body’s immune system to attack cancer. Their studies have led to the development of an entire class of drugs that hopefully will bring lasting remissions to many patients who had run out of options.